Mechanistic, kinetic, and process investigation of galactose isomerization to tagatose - Babaei, Seyedamirreza (My University, 2026)
The increasing prevalence of obesity and metabolic disorders has intensified the demand for low-calorie sugar alternatives that maintain the sensory properties of sucrose. D-Tagatose, a rare ketohexose derived from D-galactose, possesses approximately 92% of the sweetness of sucrose while providing significantly lower caloric value (1.5 kcal g⁻¹) and an extremely low glycemic index (3). Despite these advantages, large-scale production of tagatose remains limited by inefficient conversion processes and an incomplete understanding of the reaction pathways governing galactose isomerization. This thesis investigates the conversion of galactose to tagatose through CaO-mediated alkaline systems and develops a kinetic and thermodynamic framework to describe the underlying reaction network. In the first part of this work, a CaO-mediated reaction system was investigated for the isomerization of galactose under mild aqueous conditions. Using a 0.5 M galactose solution with a CaO/galactose molar ratio of 1/1, the reaction achieved 86.65% galactose conversion with 50.47% tagatose selectivity after 30 min, corresponding to a tagatose yield of 43.73%. Mechanistic observations indicate that CaO primarily acts as a source of hydroxide ions that initiate the formation of enediol intermediates responsible for aldose–ketose rearrangement. Subsequent coordination between Ca²⁺ species and galactose hydroxyl groups may further influence reaction pathways and product distribution. Process evaluation of the system indicated a minimum selling price of approximately $0.80–0.85 kg⁻¹, depending on the neutralization strategy, while life-cycle assessment showed that CO₂ neutralization reduced the global warming potential to approximately 0.90 kg CO₂-eq kg⁻¹ of tagatose. The second part of this study examines the kinetics and thermodynamics of galactose isomerization using a homogeneous triethylamine system to isolate the intrinsic reaction behavior. Experiments conducted between 40 and 100 °C were described using a reversible reaction network involving galactose, tagatose, and talose together with irreversible degradation pathways. The forward rate constant for galactose-to-tagatose conversion increased from 2.44 × 10⁻⁵ to 4.58 × 10⁻⁴min⁻¹ across the studied temperature range. Arrhenius analysis yielded activation energies of 50.6 kJ mol⁻¹ for the galactose–tagatose isomerization step and 73.1 kJ mol⁻¹ for the tagatose–talose epimerization pathway. Thermodynamic analysis indicated that the isomerization reactions are endothermic and entropy-driven, with equilibrium strongly influenced by temperature. Overall, this work provides new insights into the reaction pathways, kinetics, and process performance of galactose isomerization to tagatose. By integrating reaction system development, kinetic modeling, techno-economic analysis, and life-cycle assessment, this study establishes a framework for improving the efficiency and sustainability of rare sugar production.
Keywords: Sugar isomerization; Kinetic analysis; Techno economic analysis; Life cycle assessment